Dispersion and release of embelin from electrospun biodegradable, polymeric, membranes - Cortez Tornello, Pablo Roberto (2012)
In this work, microfiber meshes containing embelin, a poorly water-soluble bioactive agent, were prepared by solubilizing embelin in a biodegradable and biocompatible polymer matrix of poly(ε-caprolactone) (PCL). Plain or drug-loaded, highly porous, fibrous membranes with a high area-to-volume ratio were obtained by electrospinning. Non-woven microfibrous meshes were formed by uniform bead-free fibers with a mean diameter of 1.2 μm. Non-porous films were obtained by solution casting, and were used for comparison. The drug-loading content of the prepared systems was appropriate for topical applications. The thermal properties revealed that the crystallinity of embelin significantly decreased, the drug having almost completely dissolved in the PCL fibers. The in situ bioavailability of embelin, an antimycotic agent, is an important aspect to consider in topical drug applications. The drug-loaded systems presented different contact areas with the biological environment. When comparing the ability to expose embelin with the biological environment of the prepared systems, drug-loaded fibrous scaffolds showed a higher bioavailability of the bioactive agent because of an increase by 86% in the area-to-volume ratio, providing an effective area per unit mass that was 5.8-fold higher than that of the film. For the meshes, 90% embelin release was observed after 12h of exposure to phosphate-buffered saline, whereas for the films a comparable level of release occurred only after 72h.